2007
DOI: 10.1186/1471-2199-8-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Oct1 orthologue in the channel catfish, Ictalurus punctatus: A negative regulator of immunoglobulin gene transcription?

Abstract: Background: The enhancer (Eμ3') of the immunoglobulin heavy chain locus (IGH) of the channel catfish (Ictalurus punctatus) has been well characterized. The functional core region consists of two variant Oct transcription factor binding octamer motifs and one E-protein binding μE5 site. An orthologue to the Oct2 transcription factor has previously been cloned in catfish and is a functionally active transcription factor. This study was undertaken to clone and characterize the Oct1 transcription factor, which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These results reinforce that gene stability could be influenced by different factors, such as age, tissue and conditions [35,49]. Furthermore, the HPRT1 gene was classified as the least stable gene by the three software, although this gene has already been considered a good reference gene for different swine tissues [54] and mice [55], and is widely used in rats as a reference gene in qPCR studies.…”
Section: Plos Onementioning
confidence: 57%
See 2 more Smart Citations
“…These results reinforce that gene stability could be influenced by different factors, such as age, tissue and conditions [35,49]. Furthermore, the HPRT1 gene was classified as the least stable gene by the three software, although this gene has already been considered a good reference gene for different swine tissues [54] and mice [55], and is widely used in rats as a reference gene in qPCR studies.…”
Section: Plos Onementioning
confidence: 57%
“…However, Nakayama et al [ 51 ] and Nascimento et al [ 35 ] found similar results from our study, where the RPLP1 was suitable for normalization of gene expression in nasal tissue in humans and muscle tissue in broilers, respectively. Furthermore, some studies that evaluated the stability of the HMBS gene found this gene to be one of the most stable when considering several tissues [ 34 , 35 , 49 , 52 54 ]. Zhang et al [ 52 ], for example, evaluating the stability of eight reference genes in 10 types of Boer goat tissues found that the HMBS gene was the third most stable and therefore recommended this gene for calibrating gene expression analyses of goat tissues from this breed by real-time qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAD50 is a crucial protein enrolled in DNA repair [ 42 ]. RTEL is a DNA helicase which functions in the stability, protection and elongation of telomeres [ 43 ]. TERC is a critical component of telomerase complex, which provides RNA template for the telomere elongation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Octamer transcription factor 1 (Oct1; gene symbol pou2f1 ), a homeologous transcription factor of Oct4 [ 4 ], is comprised in the Pit-Oct-Unc (Pit1, Oct1/2, Unc86) family, which possesses similar in vitro DNA binding specificity [ 5 ]. Through binding to the canonical DNA motif (ATGCAAAT), OCT1 affects the transcription of a number of genes, like the immunoglobulin genes in B lymphocytes [ 6 , 7 ], some interleukins [ 8 10 ], and Pit-1 [ 11 ]. As a cis -factor, OCT1 is also required in embryogenesis and maintaining stem cell function in vivo [ 12 ].…”
Section: Introductionmentioning
confidence: 99%